Social disparities in exposures to neighbourhood obesogenic built environments in Czechia - Bartoskova Polcrova, Anna; Lam, Thao Minh; Pikhart, Hynek; Lakerveld, Jeroen (Journal of public health (Oxford, England), 2025)
BACKGROUND: Exposure to the environments with limited walkability and high density of unhealthy food outlets promotes obesity development and might cluster in disadvantaged neighbourhoods. This study examines the combined obesogenicity of urban neighbourhoods in Brno, and related socio-economic disparities. METHODS: This study was conducted in Brno, the second-largest city in Czechia. The obesogenic index was calculated from 12 components of built food and physical activity environments for each of the 296 basic settlement units (BSUs) of Brno. The index ranged from 0 (low obesogenicity) to 100 (high obesogenicity). The social disparities were assessed using linear regression. Spatial clustering was assessed using the global Moran's Index. RESULTS: The median obesogenic index score for Brno's 296 BSUs was 72.09 (IQR = 24.03), with higher scores in peripheral and industrial areas. Areas with higher proportion of people with university education had lower obesogenic scores of physical activity and overall obesogenic environment. Simultaneously, localities with higher unemployment exhibited lower obesogenic score in food and overall obesogenic environment. CONCLUSION: Areas with lower levels of obesogenicity were primarily concentrated in central locations. No clear socio-economic gradient was observed, although proportion of university-educated inhabitants and unemployment rates were both associated with lower obesogenic environment scores.
Keywords: charakteristiky okolí bydliště; Adult; cvičení; Residence Characteristics; Built Environment; Česká republika; socioekonomické faktory; Humans; ženské pohlaví; dospělí; disparity zdravotního stavu; Female; socioeconomics factors; obezita; Obesity; mužské pohlaví; vytvořené prostředí; Male; Exercise; Health Status Disparities; obesity; lidé středního věku; environment; Czech Republic; Middle Aged; charakteristiky bydlení; lidé; Socioeconomic Factors; Neighborhood Characteristics